2011
DOI: 10.1007/s12253-011-9428-1
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Poly (ADP-Ribose) Glycohydrolase (PARG) Expression Inhibits Growth of Human Colon Cancer Cells In Vitro via PI3K/Akt/NFκ-B Pathway

Abstract: Poly ADP-ribose polymerase (PARP) which is closely related to Poly ADP-ribose glycohydrolase (PARG) has already been thoroughly investigated in both experimental and clinical cancer trials compared to the latter. Nevertheless, in this experiment the importance of PARG expression was highlighted; whereby it is being silenced via lentivirus vector-mediated short hairpin RNA (shRNA). MTT assay showed that there was an inhibition in human Lovo colon cancer cell growth and flow cytometry demonstrated an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…cruzi persists in the host. It has been recently published that phosphorylated cytoplasmic IκBα is diminished in shRNA PARG Lovo cells and consequently the intranuclear expression of NF-κB p65 and the total protein expression of the latter are decreased [37]. Al-Halabi et al [38] have demonstrated that treatment with gallotannins inhibits NF-κB and slows the growth of human colon cancer xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…cruzi persists in the host. It has been recently published that phosphorylated cytoplasmic IκBα is diminished in shRNA PARG Lovo cells and consequently the intranuclear expression of NF-κB p65 and the total protein expression of the latter are decreased [37]. Al-Halabi et al [38] have demonstrated that treatment with gallotannins inhibits NF-κB and slows the growth of human colon cancer xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…A strong case can be made for the importance of the biomedical implications of the inhibition of PARG in the field of cancer therapy. For example, the absence or inhibition of PARG has been shown to arrest the metastasis of cancer cells in the human colon and in murine models, the death of BRCA-2 tumor cells (487,488), and cell death of homologous repair-deficient tumor cells (489). PARG silencing led to a reduction in PARP expression and a decrease in signaling through the phosphatidylinositol (PI) 3-kinase/Akt pathway, mediated through a reduction in NF-B (487).…”
Section: Role Of Pargmentioning
confidence: 99%
“…Supporting these rationale for Parg inhibition being a novel approach for anti-cancer therapy are several reports indicating Parg inhibition has potent anti-tumor effects against cholangiocarinoma in vivo (Marienfeld et al, 2003), and in vitro data showing growth inhibitory activity of Parg inhibition or knockdown in multiple types of cancer (Fauzee et al, 2012; Feng et al, 2012; Li et al, 2012; Pan et al, 2012). Now that the crystal structure of Parg has been solved (Slade et al, 2011; Kim et al, 2012), there is a clear need to develop specific inhibitors of this enzyme and test their efficacy as anti-cancer therapeutics.…”
Section: Clinical Modulation Of the Poly(adp)ribose Pathway: Future Pmentioning
confidence: 93%